Validated high performance liquid chromatographic (HPLC) method for analysis of zerumbone in plasma - Mohammad Eid, Eltayeb Elamin; Abdul, Ahmad Bustamam; Al-Zubairi, Adel Sharaf; Sukari, Mohamed Aspollah; Abdullah, Rasedee (Academic Journals, 2010)
Zerumbone (ZER) is a sesquiterpene derived from Zingiber zerumbet smith, family Zingiberaceae. It has been shown to possess anti-cancer and apoptosis-inducing properties against various human tumour cells as well as in vivo against a number of induced malignancies in mice. In this study a simple, specific and accurate high performance liquid chromatographic method for determination of ZER in micro-volumes human plasma (| 1.5 ml) was developed and validated. ZER and its analogue α-Humulene as internal standard were easy recovered by simple one step plasma protein precipitation using acetonitrile and separated in isocratic mobile phase, on reverse phase-C18 column. The effluent was monitored by Photodiode Array (PDA) detector and at a flow rate of 1.0 ml/min. The linearity of proposed method was 2 – 15 µg/ml. The intra-day and inter-day coefficient of variation and percent error values of the method were less than 15% and mean recovery was more than 90% for both ZER and α-Humulene. This method was found to be precise, specific, accurate and robust for detection and analysis of ZER in human plasma.